Use the expansion (x + y)^n = `sum_(k=0)^n C(n, k) x^(n - k)*y^k`

The constant term for (3x^2 + 1/x)^9 is a term with no factors of x. This arrived at when `x^(18 - 2k)/x^k = 1`

=> 18 - 2k = k

=> 18 = 3k

=> k =...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Use the expansion (x + y)^n = `sum_(k=0)^n C(n, k) x^(n - k)*y^k`

The constant term for (3x^2 + 1/x)^9 is a term with no factors of x. This arrived at when `x^(18 - 2k)/x^k = 1`

=> 18 - 2k = k

=> 18 = 3k

=> k = 6

C(9, 6) = `(9!)/((6!)*(3!))` = `(9*8*7)/(3*2)` = 84

**The constant term is 3^3*84 = 2268 **